2018
DOI: 10.1371/journal.pone.0204162
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human papillomavirus and its prognostic value in vulvar cancer: A systematic review and meta-analysis

Abstract: The purpose of this study was to estimate the prevalence of human papillomavirus (HPV) in vulvar cancer and determine whether positive HPV in vulvar cancer was associated with a better prognosis. Literature searches of Ovid EMBASE, PubMed, Web of Science and Cochrane Library were performed to identify related studies published from January 2000 to May 2017. A total of 33 studies including 7,721 subjects were selected in this meta-analysis. Overall, the HPV prevalence in vulvar cancer tissue was 34% (95% CI: 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 46 publications
(23 reference statements)
4
24
0
1
Order By: Relevance
“…Similar findings could be shown in a Scottish single-center study, where Wakeham et al reported a prognostic benefit on the clinical outcome of HPV-positive vulvar cancer [7]. In a meta-analysis including 7.721 patients, Zhang et al supported these results [8]. In a recently published Dutch study, Hinten et al described the combination of HPV and p16 ink4a positivity as a favorable prognostic factor in IVC [9].…”
Section: Introductionsupporting
confidence: 64%
“…Similar findings could be shown in a Scottish single-center study, where Wakeham et al reported a prognostic benefit on the clinical outcome of HPV-positive vulvar cancer [7]. In a meta-analysis including 7.721 patients, Zhang et al supported these results [8]. In a recently published Dutch study, Hinten et al described the combination of HPV and p16 ink4a positivity as a favorable prognostic factor in IVC [9].…”
Section: Introductionsupporting
confidence: 64%
“…Mucosal HR-HPV types have been clearly associated with the development of a small subset of VSCC. However, the contribution of the viral infectious agents appears to vary in different geographical regions [15]. In particular, limited information is available for the contribution of HR-HPV to VSCC development in Italy.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a pooled prevalence rate of HPV DNA, 34% of vulvar cancers have been reported to be attributable to HPV [15].…”
Section: Introductionmentioning
confidence: 99%
“…HPV-status, for example, might be an explanation for the increasing rate of LN metastasis with higher age. In older women HPVnegative tumors are more frequent and these are associated with shorter disease free survival [14]. Previous results are conflicting and based on small studies [11].…”
Section: Discussionmentioning
confidence: 99%